Bis(oxalato)dioxovanadate(V) and bis(oxalato)oxoperoxo-vanadate(V) complexes: spectroscopic characterization and biological activity - León, Ignacio Esteban (2013)
Two structurally related vanadium(V) complexes, K3[VO2(C2O4)2]·3H2O and K3[VO(O2)(C2O4)2]·1/2H2O, were thoroughly characterized by infrared, Raman, and electronic spectroscopies. The effect of both complexes on the viability of the human MG-63 osteosarcoma cells was tested using the MTT assay. The monoperoxo complex shows a very strong antiproliferative activity (at 100-μM concentration, this complex diminished the cell viability ca. 80 %), whereas the dioxo complex was inactive.